Does 17-α-hydroxyprogesterone Caproate Affect Fetal Birth Weight and Biometry in Singleton Pregnancies? [29R]. (May 2016) - Samson, Fernand; Tate, Danielle L.; Gomez, Luis M.
Abstract : INTRODUCTION: We sought to investigate the effects of 17-alpha-hydroxyprogesterone caproate (17P) on fetal weight and biometry in singleton pregnancies. METHODS: Retrospective cohort study, single institution, from 2010–2014. Cohort was composed by women with singletons and history of spontaneous preterm birth requiring 17P from week 16–22 until week 36 or delivery. Controls (4 per 1 cohort) were matched by gestational age at delivery and included women not on 17P and no history of prematurity. Birthweight (BW), head and abdominal circumference (HC, AC) and femur length (FL) were compared. T tests and regression analyses were performed. RESULTS: 18, 351 women delivered in our institution during the study period. We had data available for 257 women using 17P and 1, 028 randomly selected controls. Median gestational age at delivery was 37.2 (17P) and 38.5 weeks (controls); P <.001. Median BW was lower for 17P users (2, 790 gms) than controls (3, 030 gms); P <.001. After adjusting for various confounders, the difference in BW persisted lower for 17P users ( P =.02). Fetal biometry was not different among groups. There was no difference in NICU length of stay. CONCLUSION: The use of 17P may be associated with lower BW at birth but appears of no clinical significance.